Effect of some cultural practices in improving nitrogen use efficiency and Productivity of Two Varieties of Durum Wheat (Triticum durum var. turgidum L.) under Rainfed Conditions (Journal of Hama University, 2021)
This study was carried out in the Farm of  Abi- Jarash - the Faculty of Agriculture, University of  Damascus during two consecutive growing seasons (2016-2017/ 2018-2019) to study the effect of Three Levels of nitrogen fertilization (0,120,180 kg N. ha-1) and two planting dates (15 November and 15 December) on yield and its components for two varieties of  Durum Wheat (Douma1, Bohooth11). The experiment was laid out according to randomized complete block design with splite plot arrangement, with three replicates.  The Interaction between the varieties, growing seasons and planting dates with the nitrogen fertilizer rates, Grain yield 1000- kernel weight was significantly higher in the variety Douma1 for the first season and  early planting date (15 November) at the nitrogen fertilizer rate 180 kg. ha-1 (69.09 g). It can be also noticed that Grain yield was significantly higher in the variety Douma1, for the  second season  and early planting date at the nitrogen fertilizer rates (180, 120 kg. ha-1) (8620.0, 8120.0 kg. ha-1, respectively).leaf area index was significantly higher in both varieties Douma1and Bohooth11, for the first season  and early planting date at the nitrogen fertilizer rate (180 kg. ha-1) (3.97, 3.78, respectively). Nitrogen use efficiency was significantly higher in the variety Douma1, for the second season  and early planting date at the nitrogen fertilizer rate (120 kg. ha-1) (67.7). Results indicated the importance of optimizing the cultural practices to improve the quantitative characteristics of durum wheat varieties under Rainfed conditions.